Intangible Assets Disclosure By Russian And Kazakhstani Oil Companies; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 38 : Lifelong Wellbeing in the World (WELLSO 2017) - Zolotareva G. A. Galina Alekseevna (2018, 2018)
Title screen